Impact of the COVID-19 Pandemic on Global TAVR Activity: The COVID-TAVI Study - Armario, Xavier; Carron, Jennifer; Simpkin, Andrew J; Elhadi, Mohamed; Kennedy, Ciara; Abdel-Wahab, Mohamed; Bleiziffer, Sabine; Lefèvre, Thierry; Wolf, Alexander; Pilgrim, Thomas; Villablanca, Pedro A; Blackman, Daniel J; et al. (JACC. Cardiovascular interventions, 2024)
BACKGROUND: The COVID-19 pandemic adversely affected health care systems. Patients in need of transcatheter aortic valve replacement (TAVR) are especially susceptible to treatment delays. OBJECTIVES: This study sought to evaluate the impact of the COVID-19 pandemic on global TAVR activity. METHODS: This international registry reported monthly TAVR case volume in participating institutions prior to and during the COVID-19 pandemic (January 2018 to December 2021). Hospital-level information on public vs private, urban vs rural, and TAVR volume was collected, as was country-level information on socioeconomic status, COVID-19 incidence, and governmental public health responses. RESULTS: We included 130 centers from 61 countries, including 65,980 TAVR procedures. The first and second pandemic waves were associated with a significant reduction of 15% (P < 0.001) and 7% (P < 0.001) in monthly TAVR case volume, respectively, compared with the prepandemic period. The third pandemic wave was not associated with reduced TAVR activity. A greater reduction in TAVR activity was observed in Africa (-52%; P = 0.001), Central-South America (-33%; P < 0.001), and Asia (-29%; P < 0.001). Private hospitals (P = 0.005), urban areas (P = 0.011), low-volume centers (P = 0.002), countries with lower development (P < 0.001) and economic status (P < 0.001), higher COVID-19 incidence (P < 0.001), and more stringent public health restrictions (P < 0.001) experienced a greater reduction in TAVR activity. CONCLUSIONS: TAVR procedural volume declined substantially during the first and second waves of the COVID-19 pandemic, especially in Africa, Central-South America, and Asia. National socioeconomic status, COVID-19 incidence, and public health responses were associated with treatment delays. This information should inform public health policy in case of future global health crises.
Keywords: Pandemics; Aortic Valve; výsledek terapie; coronavirus disease 2019; registrace; COVID-19; Transcatheter Aortic Valve Replacement; valvular heart disease; transkatetrální implantace aortální chlopně; aortální chlopeň; Registries; Aortic Valve Stenosis; aortic valve stenosis; transcatheter aortic valve replacement; Humans; rizikové faktory; aortální stenóza; pandemie; Risk Factors; Treatment Outcome; lidé